SOCIAL SUPPORT, QUALITY OF LIFE AND MENTAL HEALTH PROBLEMS AMONG FEMALES WITH AND WITHOUT MENSTRUATION PROBLEMS: A COMPARATIVE STUDY - Sarwar, Uzma; Rauf, Umara (KHYBER MEDICAL UNIVERSITY JOURNAL, 2021)
OBJECTIVE: To access the social support, quality of life (QoL) and mental health problems to discriminate between females with and without menstruation problems. METHODS: This comparative study was conducted on sample of 408 females enrolled in study through purposive sampling technique. Female (with and without problems of menstruation) aging from 13 to 40 years, without any restriction of socioeconomic status were recruited in study from public and private academic institutions and hospitals of Sialkot, Pakistan. Females who denied giving consent and those who had any other chronic and infectious disease like diabetes, heart disease, cancer etc. were excluded from the study. Demographic variables detail, Multidimensional Scale of Perceived Social Support (MPSS), QoL and Depression Anxiety and Stress Scale (DASS) were assessed. Results was analyzed by using SPSS version 20. RESULTS: Out of 408 participant, 206 (50.5%) were with menstruation problems and 202 (49.5%) without problem. Majority (n=146; 35.8%) were form 19-26 years age group. Around 38.5% (n=157) were graduates. Majority (n=355; 87.0%) were from middle class families. Common menstrual problems observed were dysmenorrhea (n=77; 18.9%), oligomenorrhea (n=67; 16.4%) and menorrhagia (n=62; 15.2%). Significant difference among females with and without menstruation problems were found on the variables of quality of life (t= 5.01, p< 0.05) and mental health problems (t=-3.88, p< 0.05). CONCLUSION: Females with menstruation problems suffers with mental health problems and poor QoL than females without menstruation problems. There is immense need to deal with mental health issues of this group to enhance QoL.